Skeletal Muscle myomiR Are Differentially Expressed by Endurance Exercise Mode and Combined Essential Amino Acid and Carbohydrate Supplementation - Margolis, Lee M.; McClung, Holly L.; Murphy, Nancy E.; Carrigan, Christopher T.; Pasiakos, Stefan M. (Frontiers in Physiology, 2017)
Skeletal muscle microRNAs (myomiR) expression is modulated by exercise, however, the influence of endurance exercise mode, combined with essential amino acid and carbohydrate (EAA+CHO) supplementation are not well defined. This study determined the effects of weighted versus non-weighted endurance exercise, with or without EAA+CHO ingestion on myomiR expression and their association with muscle protein synthesis (MPS). Twenty five adults performed 90 min of metabolically-matched (2.2 VO2 L∙m-1) load carriage (LC; performed on a treadmill wearing a vest equal to 30% of individual body mass) or cycle ergometry (CE) exercise, during which EAA+CHO (10 g EAA and 46 g CHO) or non-nutritive control (CON) drinks were consumed. Expression of myomiR (RT-qPCR) were determined at rest (PRE), immediately post-exercise (POST), and 3 h into recovery (REC). Muscle protein synthesis (2H5-phenylalanine) was measured during exercise and recovery. Relative to PRE, POST and REC expression of miR-1-3p, miR-206, miR-208a-5 and miR-499 was lower (P < 0.05) for LC compared to CE, regardless of dietary treatment. Independent of exercise mode, miR-1-3p and miR-208a-5p expression were lower (P < 0.05) after ingesting EAA+CHO compared to CON. Expression of miR-206 was highest for CE-CON than any other treatment (exercise-by-drink, P < 0.05). Common targets of differing myomiR were identified as markers within mTORC1 signaling, and miR-206 and miR-499 were inversely associated with MPS rates immediately post-exercise. These findings suggest the alterations in myomiR expression between exercise mode and EAA+CHO intake may in part be due to differing MPS modulation immediately post-exercise.